Position Of Human Capital In Middle-Income Trap Countries (Case Study: Indonesia) - et. al., Tria Apriliana, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The middle income trap explains that an economy that reaches the middle income level has been at this level for many years and has not grown to a higher income level. Human capital has a special role in the model of economic improvement. This study aims to examining more deeply the role of human capital in determining Indonesia's position in the country with Middle Income Trap. This research used simple and multiple linear regression analytical tools. The results show the 13-15 year old group had a positive effect on GDP per capita growth. Meanwhile, the 16-18 year age group has a positive effect on GDP per capita growth. Only the Illiteracy number 45 years old has a positive effect on GDP per capita growth because it is a productive group. The level of the Human Development Index has a positive effect on GDP per capita because it reflects the level of community empowerment that can increase productivity.